Investigation of the Composting Process of Mongolian Horse Manure Utilizing Intelligent Composting Equipment - Jian Wang; Kailin Ren; Yong Zhang; Longfei Zhang; Zhe Li (Agronomy)
The Inner Mongolia Autonomous Region, known for its famous Mongolian horses, faces significant environmental challenges due to the large-scale rearing of these animals, which produces a substantial amount of manure. If not managed effectively, this manure can lead to severe environmental pollution. The aim of this study was to investigate whether a small-scale intelligent aeration and heating composting system is effective in treating Mongolian horse manure, with the objective of enhancing composting efficiency and resource utilization to support sustainable agricultural development in the region. The equipment was utilized to treat a compost mixture of Mongolian horse manure and corn stover, allowing for an analysis of the changes in key indicators throughout the composting process. The results demonstrated that the equipment maintained high temperatures for up to eight days during the composting process, effectively inactivating pathogens and promoting the efficient decomposition of organic matter. The system also successfully controlled humidity to 12.7% and maintained oxygen concentration within the optimal range. Post-composting analysis revealed that the final compost contained 2.3% nitrogen, 1.3% phosphorus, and 1.2% potassium, with a pH of 6.4 and conductivity of approximately 5.2 mS/cm. Additionally, the carbon-to-nitrogen ratio decreased significantly from 27.3 to 15.9, indicating substantial organic matter degradation. Seed germination tests showed germination rates of 80%, 86%, and 75% for corn, mung bean, and wheat, respectively, with a final seed germination index of 104%. This study concluded that the small aeration and heating composting equipment is highly effective in treating Mongolian horse manure, producing high-quality organic fertilizers that significantly enhance soil fertility and demonstrate considerable potential for supporting sustainable agricultural practices and improving environmental management in the Inner Mongolia Autonomous Region.